A psychosocial analysis of relational aggression in Mexican adolescents based on sex and age - Romero Abrio, Ana; Martínez Ferrer, Belén; Sánchez Sosa, Juan; Musitu, Gonzalo (Colegio Oficial de Psicología del Principado de Asturias, 2019)
This paper aims to identify predictive variables of relational aggression related to the individual, family and school environment in Mexican adolescents according to sex and age. Method: A total of 8,115 Mexican adolescents (51.5% boys), aged 11 to 16 years old (M = 13.34 years, SD = 1.040), selected by proportional stratified sampling. Results: From a stepwise regression analysis it was observed that the main predictors of relational aggression were non-conformist self-perception of social reputation, psychological distress, attitude toward institutional authority and offensive communication with the mother. Conclusions: Relational aggression underlies important explanatory dimensions for the prevention of school aggression, such as social reputation and psychological distress, which have been little explored in this field of study.